Gaming - Berikoff, Ahna (My University, 2020)
In this episode of Pass the Mic, 4th year students Vivian, Andrew and Emele discuss their involvement with gaming. They shed light on the benefits of gaming as a virtual means for connection, skill development and adventure.
1 streaming audio file (42:50 min.) : mp3 : digital file.